Intravitreal anti-VEGF injections for treating wet age-related macular degeneration: a systematic review and meta-analysis - Ba J; Peng RS; Xu D; Li YH; Shi H; Wang QY; Yu J (Dove Medical Press, 2015)
Jun Ba,1,2,* Run-Sheng Peng,2,* Ding Xu,1 Yan-Hong Li,1 Hui Shi,1,3 Qianyi Wang,1 Jing Yu11Department of Ophthalmology, Shanghai Tenth People’s Hospital Affiliated with Tongji University, 2Department of Cardiac Surgery, Institute of Cardiovascular Diseases of Fudan University, Affiliated Zhongshan Hospital of Fudan University, Shanghai, People’s Republic of China; 3Department of First Clinical Medical College, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China*Co-first authors of this workAims: Age-related macular degeneration (AMD) is the main cause of blindness. Anti-vascular endothelial growth factor is used to prevent further neovascularization due to wet AMD. The purpose of this systematic review was to investigate the effect and protocol of anti-vascular endothelial growth factor treatment on wet AMD.Methods: A comprehensive literature search was performed in PubMed, Embase, the Cochrane Library, CNKI, and reference lists. Meta-analysis was performed using Stata12.0 software, best corrected visual acuity (BCVA), retinal thickness, and lesion size were evaluated.Results: Twelve randomized controlled trials spanning from 2010 to 2014 and involving 5,225 patients were included. A significant difference was observed between the intravitreal ranibizumab (IVR) group and the intravitreal bevacizumab group (standard mean difference =-0.14, 95% confidence interval [CI] =-0.23 to -0.05). No significant differences were observed in best corrected VA, retinal thickness, or lesion size between IVR and the intravitreal aflibercept group. Compared to monthly injection, IVR as-needed injections (PRN) can raise VA by 1.97 letters (weighted mean difference =1.97, 95% CI =0.14–3.794). Combination therapy of IVR and photodynamic therapy can significantly raise VA by 2.74 letters when combined with IVR monotherapy (weighted mean difference =2.74, 95% CI =0.26–5.21).Conclusion: The superiority remains unclear between IVR and intravitreal bevacizumab in the treatment of neovascular AMD. Intravitreal aflibercept dosed every 2 months required fewer injection times, but produced similar efficacy as monthly IVR. IVR PRN could significantly increase VA. Combined with photodynamic therapy, IVR therapy could also increase VA effectively.Keywords: age-related macular degeneration, VEGF, ranibizumab, bevacizumab, aflibercept, meta-analysis